If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2(c + -8) Reorder the terms: 10 = 2(-8 + c) 10 = (-8 * 2 + c * 2) 10 = (-16 + 2c) Solving 10 = -16 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 10 + -2c = -16 + 2c + -2c Combine like terms: 2c + -2c = 0 10 + -2c = -16 + 0 10 + -2c = -16 Add '-10' to each side of the equation. 10 + -10 + -2c = -16 + -10 Combine like terms: 10 + -10 = 0 0 + -2c = -16 + -10 -2c = -16 + -10 Combine like terms: -16 + -10 = -26 -2c = -26 Divide each side by '-2'. c = 13 Simplifying c = 13
| 2(-7b+3)=-3-5b | | (6-2i)-(8-1/4i) | | y=15000 | | -2b+10=-b | | p*5=6*q | | -9-2v=5-4v | | 4rx+ry+8sx+2sy= | | 4(a-2)-9=14 | | 8x+3x=5 | | 6u=7u+9 | | 2log(2x-1)=2 | | -3-10r=9r | | -3-10r=-93 | | 5x+40=10x | | -p+8=p | | 7x+8=5x+40 | | 7k-14=3(1+8k) | | X+3=5x+-4 | | 40-6x=24 | | 991/1000x100 | | 75x+3-28=0 | | -2x+6y=13 | | 7c(5c+7)=0 | | 75x-25=0 | | 5x+10*50=800 | | 27-4x=2x+4 | | 2xy+3xz+xy=0 | | 7x-3=9x+23 | | 6(1-8a)=-40-2a | | 5x-4(2x+1)=-10 | | x=4(x-66) | | 60p^2-246p+126=0 |